Favoriser l’agentivité des étudiants dans des cours par visioconférence pendant la crise sanitaire : relation interpersonnelle et agir éthique - Catherine Muller (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
This article focuses on student agency during video-mediated foreign language classes that took place during the pandemic. My aim is to understand how learners were able to deploy their agency in this constrained context, during which online teaching was mandatory. How does the interpersonal relationship established between the interactants, characterised by ethical action, contribute to the participants’ engagement and agency? After presenting a theoretical framework on remote social presence and agency in digital learning environments, I outline the methodology adopted, which is based on self-observation of three master's courses during the 2020–2021 academic year and a three-stage qualitative cross-analysis. First, I study the students’ initiatives, which show a strong engagement and lead to a negotiation of the didactic contract. I then analyse group work on the basis of two practical questions that emerged, and approach them from an ethic perspective as well. In the final section, I show how the students recognise the teacher’s ethical action and highlight her role in the participants’ commitment.